Enhancing healthcare interoperability in Central Europe: implementing IHE profiles in University Hospital Trenčín, University Hospital Olomouc, and CKTCH Brno - Zubek, Martin; Svobodová, Romana; Jeřábek Csc, Jaroslav; Hána, Karel; Prettner, Kateřina; Hrdlička, Filip (International Journal of Electronics and Telecommunications, 2026)
Healthcare interoperability remains a major challenge in Central Europe, where fragmented information systems and legacy data formats hinder efficient clinical data exchange. Despite advances in electronic health records (EHRs) and ePrescription systems, interoperability between institutions in Slovakia and the Czech Republic remains limited. Objectives: This study aims to demonstrate how international interoperability frameworks specifically Integrating the Healthcare Enterprise (IHE) profiles and HL7 Fast Healthcare Interoperability Resources (FHIR)—can enhance secure data sharing, patient identification, and clinical collaboration in Central European hospitals. Methods: A qualitative, multi-case analysis was performed across three hospitals: University Hospital Trenčín (Slovakia), University Hospital Olomouc, and the Centre for Cardiovascular and Transplant Surgery (CKTCH) Brno (Czech Republic). Each site implemented selected IHE profiles (XDS.b, PIX, ATNA, XCA, XCPD, XUA) and FHIR APIs to support document sharing and patient identity reconciliation. System architectures, project documentation, and stakeholder feedback were evaluated to assess performance and scalability. Results: The Proof-of-Concept in Trenčín achieved a 45% reduction in document retrieval time and improved patient identification accuracy. The Czech deployments in Olomouc and Brno demonstrated successful cross-institutional access to patient records and reduced diagnostic duplication. All implementations were built using standards-compliant commercial solutions, demonstrating scalability, vendor neutrality, and alignment with the European Health Data Space (EHDS) framework. Conclusions: The study provides empirical evidence that IHE and FHIR integration substantially improves interoperability and clinical efficiency in multi-institutional healthcare networks. The presented architecture serves as a reusable blueprint for national-level digital health infrastructures, supporting future EHDS implementation and secondary data use across Central Europe.